Study of post annealing effects on structural and optical properties of sol-gel derived ZnO thin films grown on n-Si substrate - Yadav, Aniruddh Bahadur; Periasamy, C.; Jit, S. (Institute of Physics Publishing, 2015)
Zinc oxide (ZnO) thin films were grown on n-type silicon (100) substrates by sol- gel spin coating technique. The prepared thin films were annealed in the presence of Ar at three different temperatures (at 450°C, 550°C and 650°C) to study the impact of annealing temperature on the structural and optical properties of the ZnO thin films. The structural, surface morphology and optical properties of the thin film were investigated using X-ray diffraction (XRD), scanning electron microscopy (SEM) and photoluminescence (PL) measurements respectively. The grown ZnO thin films are polycrystalline in nature with wurtzite hexagonal structure as evident from the XRD and SEM analyses. It further indicates that the crystalline size increases with increasing annealing temperature. The post annealing is also found to influence the optical properties in the terms of band gap energy of the ZnO thin films. The optical energy band gap was found to be decreased from 3.205 to 3.13eV as the annealing temperature is increased from 450°C to 650°C. However, our results concerning the growth of ZnO thin films on Si substrates suggest that there is an intermediate growth temperature allowing for the optimization of the ZnO film growth. The results of the study can be used as a guideline for growing ZnO thin films on n-Si substrates with a homogenous surface morphology, high surface to volume ratio and desired particle size, which are suited for optoelectronic/ gas sensing applications.
Keywords: Sol-gels; Scanning electron microscopy; Thin films; Zinc coatings